Cuidado ao filhote de boto cinza, Sotalia guianensis (van Benédén, 1864) - Gondim, Mariana Alves (2006)
In some species parental care is vital to survival. Many studies have reported various parental care behaviours in cetaceans. In Sotalia guianensis, some behaviours have been already described and linked to parental care. However, many aspects are still unknown and all these information might be important for the species conservation. The aim of the present study was minimize these gaps, showing the options involved in the marine tucuxi parental care. The observations took place in Enseada do Curral, located in Pipa, Tibal do Sul, Rio Grande do Norte Coast. Between January and December of 2005 the local population of tucuxi was observed during 42 days. The methods used were Focal Animal and Ad Libitum. The results suggest that calves are present in the bay all year long. Groups with calves had a mean of 6,9 animals, allowing the animals to participate in different activities in the group besides caring. The calves created different associations, being usually followed by an adult. In groups, the calves stay mainly in the centre, which offers them protection. Calves remained next to the adults tail, facilitating breastfeeding. The calves most noticeable activities were those in the surface and the behaviour frequencies decreased, in general, in the presence of human swimmers and boats, what could be considered a threat to the animals. Adults shared positions when caring for calves, suggesting allomaternal care; food transfer from adults to calves was observed, which might be related to diet acquisition; three non-described behaviours were seen, indicating a diversified behavioural repertoire for this species